In Silico Evaluation of Flavonoids from Imperata cylindrica as Potential Antidiabetic Agents - Afnani, Moh. Royhan; Sutriyansyah, Riska Ayu; Ansori, Arif Nur Muhammad (Tropical Biopharmaca Research Center, IPB University, 2026)
Diabetes mellitus is a metabolic disorder characterized by impaired insulin secretion and disrupted blood-glucose homeostasis. Novel therapies targeting the incretin system, such as dipeptidyl peptidase 4 (DPP-4) inhibitors, enhance insulin secretion, protect β-pancreatic cells, and restore glucose balance. Imperata cylindrica (reeds) has shown antidiabetic effects, including improved insulin release and reduced blood glucose, but its molecular mechanism remains unclear. This study investigated flavonoid compounds from I. cylindrica as potential DPP-4 inhibitors using molecular docking. The target protein (PDB: 6B1E) and drug-like flavonoids were evaluated via PyRx and visualized with Discovery Studio 2021. The results indicate that tricin binds strongly to DPP-4 (−8.4 kcal/mol) and forms stable interactions with residues ILEB102, ILEB76, and ILEB529. These findings suggest that tricin from I. cylindrica may inhibit DPP-4 and serve as a potential antidiabetic agent in silico.